Study on the Annual Reduction Rate of Vehicle Emission Factors for Carbon Monoxide: A Case Study of Urban Road Tunnels in Shenzhen, China - Weiwei Liu; Jianxun Chen; Yanbin Luo; Zhou Shi; Xiang Ji; Haoyang Zhu (Advances in Civil Engineering)
Environmental pollution and energy conservation in urban tunnels have become important issues that affect the scientific design and sustainable development of urban tunnels. The carbon monoxide (CO) concentration in urban road tunnels is regarded as a direct reflection and a useful tracer of the intensity of anthropogenic transportation activities. Previous studies in recent years have paid more attention to pollutant emission factors, but less to the calculation parameters of ventilation design for tunnels. This paper aims to study a reasonable annual reduction rate of CO base emission factors. Therefore, a detailed field measurement was carried out in the four typical urban road tunnels, Henglongshan Tunnel, Cejiexian Tunnel, Jiuweiling Tunnel, and Dameisha Tunnel in Shenzhen, China, from March 29 to September 16, 2014. Measurement results showed that the traffic flow of the four urban tunnels had been approaching the design value, or even beyond the limit. The average daily air velocities in the four tunnels were all within 5 m/s, whereas the maximum air velocity had exceeded the limit of 10 m/s. The CO concentrations in Henglongshan Tunnel, Cejiexian Tunnel, Jiuweiling Tunnel, and Dameisha Tunnel were 17 ppm, 7 ppm, 39 ppm, and 8 ppm, respectively. Moreover, it was found that the average CO emission factors of Henglongshan Tunnel, Cejiexian Tunnel, Jiuweiling Tunnel, and Dameisha Tunnel were 1.075 g/(km·veh), 1.245 g/(km·veh), 4.154 g/(km·veh), and 1.739 g/(km·veh), respectively. Based on the statistical data, the CO emission factors of mixed traffic and passenger cars decrease by an average of 16.4% and 33.3%, respectively, per year through the regression method and by an average of 17.4% and 29.0%, respectively, per year through the extremum method. Finally, when considering the safety factor of 20%, it is more reasonable for the CO base emission to adopt 4% as an annual reduction rate for ventilation design in urban tunnels.